2019
DOI: 10.1039/c8nj06179c
|View full text |Cite
|
Sign up to set email alerts
|

Chiral chromane[4]arenes synthesised by cycloaddition reactions ofo-quinomethine resorcin[4]arenes

Abstract: The synthesis of cavity-extended cyclochiral heterocyclic derivatives of chromane[4]arenes by a cycloaddition reaction between the o-quinomethine derivative of resorcin[4]arene and various styrenes is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…12 Among other things, spatially developed structures such as cavitands, [13][14][15][16] dimeric capsules, [17][18][19][20] and hexamers [21][22][23][24] can be constructed based on such skeletons, and these can be used to study the reactivity of chemical compounds in spatially limited or closed structures. [25][26][27][28] One possibility for modifying the structure of resorcin [4] arene was our use of the methoxy derivative of resorcin [4]arene for the thermal generation of the o-quinone methide derivative of resorcin [4]arene, followed by a cycloaddition reaction [29][30][31] and Michael reaction with C, Pnucleophiles. 32,33 Until now, the synthesis of cyclochiral derivatives of resorcin [4]arene was based on two approaches: (1) structural modications of the skeleton of the resorcin [4]arene molecule via covalent bonds; 4,5 (2) on the selection of appropriate substrates for the synthesis of cyclochiral resorcin [4]arene molecules.…”
Section: Introductionmentioning
confidence: 99%
“…12 Among other things, spatially developed structures such as cavitands, [13][14][15][16] dimeric capsules, [17][18][19][20] and hexamers [21][22][23][24] can be constructed based on such skeletons, and these can be used to study the reactivity of chemical compounds in spatially limited or closed structures. [25][26][27][28] One possibility for modifying the structure of resorcin [4] arene was our use of the methoxy derivative of resorcin [4]arene for the thermal generation of the o-quinone methide derivative of resorcin [4]arene, followed by a cycloaddition reaction [29][30][31] and Michael reaction with C, Pnucleophiles. 32,33 Until now, the synthesis of cyclochiral derivatives of resorcin [4]arene was based on two approaches: (1) structural modications of the skeleton of the resorcin [4]arene molecule via covalent bonds; 4,5 (2) on the selection of appropriate substrates for the synthesis of cyclochiral resorcin [4]arene molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier paper, 13 the possibility of synthesising 4hydroxycoumarin derivatives of resorc [4]arene was shown using the Michael reaction of the o-quinomethine derivative of resorc [4]arene, which was generated thermally from the methoxy derivative of resorc [4]arene. The resulting 4-hydroxycoumarin derivative of resorc [4]arene exhibited a variable 'in-out' conformation depending on the reaction environment.…”
Section: Resultsmentioning
confidence: 99%
“…Chromane [4] arenes were obtained by the Diels-Alder reaction between the o-quinone methides of resorcin [4] arene and styrenes [34]. The authors identified their compounds as chiral, but actually, they were racemic mixtures.…”
Section: Cycloaddition Of Ortho-quinone Methidesmentioning
confidence: 99%